2018
DOI: 10.3390/met8110882
|View full text |Cite
|
Sign up to set email alerts
|

The Annealing Twins of Fe-20Mn-4Al-0.3C Austenitic Steels during Symmetric and Asymmetric Hot Rolling

Abstract: The present work investigates the annealing twins of Fe-20Mn-4Al-0.3C austenitic steels in symmetric hot rolling (SHR) and asymmetric hot rolling (ASHR). The average grain size is 26 (±9.6) μm and 11 (±7.0) μm for the tested steel in SHR and ASHR processes. The density of high angle grain boundary (HAGB) and annealing twin boundary increase with the decrease of grain size. The annealing twin is obviously higher in ASHR than in SHR. The linear relation model between the logarithm of twin boundary density and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…From the pole diagram of Grains A and B, they have an ideal 60° orientation deviation (Figure 17c). It is generally accepted that the twin boundary migrates along the normal direction to the twin plane, [ 52 ] such as the growth direction shown in Figure 17a. Twin boundary can reduce the interface energy and improve the migration ability of grain boundary.…”
Section: Discussionmentioning
confidence: 99%
“…From the pole diagram of Grains A and B, they have an ideal 60° orientation deviation (Figure 17c). It is generally accepted that the twin boundary migrates along the normal direction to the twin plane, [ 52 ] such as the growth direction shown in Figure 17a. Twin boundary can reduce the interface energy and improve the migration ability of grain boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Twin boundaries are low energy defects compared to grain boundaries but reports in literature showed that they do have both detrimental and beneficial effects on material properties. Improved tensile strength is one of the major beneficial effects observed due to the formation of annealing twins [8,9]. According to Li and his co-workers [8], the improved tensile strength of austenitic (Fe-10Mn-4Al-0.3C) is due to combined effects of grain refinement and formation of high density of annealing twins.…”
Section: Introductionmentioning
confidence: 99%
“…Improved tensile strength is one of the major beneficial effects observed due to the formation of annealing twins [8,9]. According to Li and his co-workers [8], the improved tensile strength of austenitic (Fe-10Mn-4Al-0.3C) is due to combined effects of grain refinement and formation of high density of annealing twins. Similarly, Chuang and his colleagues [9] showed simultaneous increment of tensile strength and elongation due to emerging of large amount of annealing twins in Ag-8Au-3Pd wire.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the processes of formation of structure and properties during cold plastic deformation of MASS by rolling [8,10,11], torsional deformation [12], surface mechanical attrition treatment [13] and equal-channel angular pressing [14,15,16] have been the most commonly studied processes. These methods of strain hardening differ in the strain pattern and rate, which, as is well known, significantly affect the processes of structure formation during deformation processing, and consequently the properties of the processed steel [3,13,17,18,19]. However, structural changes and their impact on the formation of a complex of mechanical properties of MASS during cold radial forging (CRF) are currently understudied.…”
Section: Introductionmentioning
confidence: 99%